Evaluating the effectiveness and feasibility of nurse-led distant and face-to-face interviews programs for promoting behavioral change and disease management in patients with diabetic nephropathy: a triangulation approach - Kana Kazawa; Kanae Osaki; Md Moshiur Rahman; Michiko Moriyama (BMC, 2020)
Abstract Background We examined whether telecommunication-device-based distance interviews are inferior to face-to-face interviews in terms of facilitating behavioral changes and disease management in patients with diabetic nephropathy. We also examined the feasibility of a newly designed six-month telenursing program. Methods This study represents a post-hoc analysis of data from a randomized controlled trial, in which we compared the efficacy of remote self-management education with that of direct education for patients with diabetic nephropathy. The participants were 40 company employees, who were randomly divided into two groups. Over 6 months, the intervention group (n = 21) received three distance interviews using a tablet computer. Meanwhile, the control group (n = 19) received three face-to-face interviews. In addition, both groups received biweekly nine telephone calls. A triangulation approach was used. We first compared the two groups in inferiority tests. Then, we analyzed data from semi-structured interviews with all participants and nurses, examining whether trusting relationships and motivation were developed, and the accuracy of the information exchanges. Further, for the intervention group, we also enquired about the overall operability of the telenursing device. Results The completion rates for the program were 81.0 and 78.9% for the participants in the intervention and control groups, respectively. Both groups showed similar behavioral changes, and the participants verified the feasibility of the distance interviews. The participants in the intervention group felt that they understood the severity of their diseases and the necessity of self-management, and felt confidence in the nurses. On the other hand, their degree of behavioral change regarding self-monitoring was lower than that shown by the control group. Conclusion Our findings show that both interview methods are effective for encouraging the adoption of self-management; further, in terms of taking medication and improving the main clinical indicators, we found that the distance method is not inferior to the direct face-to-face method. However, when considering long-term effects, based on the respective degrees of improvement in behavioral change, the direct method seems to be more effective. Trial registration The trial was registered with the University Hospital Medical Information Network clinical trial registry (No. UMIN000026568 ) on March 15, 2017, retrospectively.